Blood pressure reference values for Brazilian adolescents: data from the Study of Cardiovascular Risk in Adolescents (ERICA Study) - Thiago Veiga Jardim; Bernard Rosner; Katia Vergetti Bloch; Maria Cristina Caetano Kuschnir; Moyses Szklo; Paulo César Veiga Jardim (Elsevier, 2020)
Objective: Blood pressure (BP) references for Brazilian adolescents are lacking in the literature. This study aims to investigate the normal range of office BP in a healthy, non-overweight Brazilian population of adolescents. Method: The Brazilian Study of Cardiovascular Risks in Adolescents (Portuguese acronym "ERICA") is a national school-based study that included adolescents (aged 12 through 17 years), enrolled in public and private schools, in cities with over 100,000 inhabitants, from all five Brazilian macro-regions. Adolescents' height and body mass index (BMI) were classified in percentiles according to age and gender, and reference curves from the World Health Organization were adopted. Three consecutive office BP measurements were taken with a validated oscillometric device using the appropriate cuff size. The mean values of the last two readings were used for analysis. Polynomial regression models relating BP, age, and height were applied. Results: Among 73,999 adolescents, non-overweight individuals represented 74.5% (95% CI: 73.3-75.6) of the total, with similar distribution across ages. The majority of the non-overweight sample was from public schools 84.2% (95% CI: 79.9-87.7) and sedentary 54.8% (95% CI: 53.7-55.8). Adolescents reporting their skin color as brown (48.8% [95% CI: 47.4-50.1]) or white (37.8% [95% CI: 36.1-39.5]) were most frequently represented. BP increased by both age and height percentile. Systolic BP growth patterns were more marked in males when compared to females, along all height percentiles. The same pattern was not observed for diastolic BP. Conclusions: Blood pressure references by sex, age, and height percentiles for Brazilian adolescents are provided. Resumo: Objetivo: Referências de pressão arterial (PA) para adolescentes brasileiros estão ausentes na literatura. Este estudo tem como objetivo investigar a variação normal da pressão arterial no consultório em uma população brasileira saudável de adolescentes sem sobrepeso. Método: O Estudo dos Riscos Cardiovasculares em Adolescentes (ERICA) é um estudo brasileiro, de âmbito nacional e de base escolar, que incluiu adolescentes (12 a 17 anos) matriculados em escolas públicas e privadas, em cidades com mais de 100.000 habitantes, de todas as cinco macrorregiões brasileiras. A altura e o índice de massa corporal (IMC) dos adolescentes foram classificados em percentis de acordo com a idade e o sexo, sendo adotadas as curvas de referência da Organização Mundial de Saúde. Foram realizadas três medidas consecutivas de PA no consultório com um dispositivo oscilométrico validado, utilizando o manguito de tamanho apropriado. Os valores médios das duas últimas leituras foram utilizados nas análises. Modelos de regressão polinomial relacionando PA, idade e estatura foram aplicados. Resultados: Entre os 73.999 adolescentes, os indivíduos sem sobrepeso representaram 74,5% (IC95%: 73,3-75,6) do total, com distribuição similar entre as idades. A maior parte da amostra sem sobrepeso originava-se das escolas públicas, com 84,2% (IC95%: 79,9-87,7), e os sedentários 54,8% (IC95%: 53,7-55,8). Os adolescentes que relataram sua cor de pele como parda (48,8% [IC95%: 47,4-50,1]) e branca (37,8%: [IC 95% 36,1-39,5]) foram os mais representados. A PA aumentou tanto com a idade, quanto com o percentil de altura. Os padrões de aumento sistólico da PA foram mais acentuados no sexo masculino quando comparados ao sexo feminino, em todos os percentis de altura. O mesmo padrão não foi observado para a PA diastólica. Conclusões: São fornecidas referências de pressão arterial por sexo, idade e percentil de altura para adolescentes brasileiros. Keywords: Pediatric, Office blood pressure, Hypertension, Blood pressure measurement/monitoring, Diagnostic method, Palavras-chave: Pediátrico, Pressão arterial no consultório, Hipertensão, Mensuração/monitorização da pressão arterial, Método diagnóstico